Glossary of Library Classification Terms: A Review of the Developments in India - Prasad, K. N. (Journal of Information and Knowledge, 1984)
Reviews the development of terms in the field of library classification in India. Based on a comparative census of the terms contained in the three editions of the Prolegomena to Library Classification (ed1; 1937. ed2; 1957; ed3; 1967). Presents a conclusion that the field of library classification conforms to the science of glossematics.